Accessible 3D Integrative Paper Electrode Shapes: All‐Carbon Dual‐Ion Batteries with Optimum Packaging Performances. Issue 12 (13th September 2017) - Shi, Xiaoyuan; Deng, Ting; Zhang, Bingsen; Zhang, Wei; Sui, Lu; Yang, He; Wang, Dong; Shi, Wen; Chen, Cheng‐Meng; Zheng, Weitao
Abstract: Dual‐ion batteries are promising devices, owing to their compatibility of high energy density and high power density, provide that the volume expansion of positive graphite and the decomposition of the electrolyte are well addressed. Herein, we report a facile strategy of using low‐cost carbon fiber paper for package enhancement of dual‐ion batteries. The three‐dimensional structure offers both conductivity and structure integrity, while the highly graphitic fiber paper endows the high intercalation potential towards high energy density. High stability results from such integrative electrode structure. Matching with electrical double‐layer capacitive graphene and ionic liquids, with a wide electrochemical stability window, a dual‐ion battery has been fabricated to achieve a specific energy of 149 Wh/kg at a specific power of 1011 W/kg, and the specific energy retains 85 % after 1000 cycles. This accessible 3D paper electrode provides a new route for an integral electrode construct that can be used in ultrastable, high‐efficiency energy‐storage devices. Abstract : Origami electrodes : A facile strategy of using carbon fiber paper (CFP) for packaging enhances the performance of dual‐ion batteries. CFP provides a highly graphic layer for ion intercalation and amorphous carbon to buffer volume changes on its unique 3D structure. The integration of a current collector as one integrated electrode offers uniform conductivity and avoids material exfoliation and negative influence of binders.